087 Initial Validation of the Radical Prostatectomy Questionnaire (RPQ): A New Patient Reported Outcome (PRO) to Assess Sexual Function Following Radical Prostatectomy (RP). (1st May 2022) - Nelson, CJ; Flaherty, K; Joshi, N; Schofield, E; Mulhall, JP
ABSTRACT: Introduction: The only PRO validated for men after RP is Extended Prostate Cancer Index (EPIC). However, EPIC has weaknesses, including the lack of assessment of function in response to ED medication use, inclusion of ejaculation and absence of penile morphology assessment. We developed the RPQ to address these weaknesses. Methods: RPQ is a 41-item scale assessing 5 domains: erectile function (EF), sexual desire (SD), orgasm (O), sexual satisfaction (SS), and penile morphology (PM). The EF domain assesses erections in response to no medication, PDE5i, intracavernosal injections (ICI). We used a multi-step process to develop the RPQ including: extensive literature review; development of primary domains; item generation and winnowing; feedback from 8 sexual medicine experts; and cognitive interviewing with 10 patients to verify content, wording, and response format. For validation, post-RP men completed the RPQ and the following PROs: IIEF, EPIC, SEAR, and the PROMISE measures. Participants completed the RPQ again within two weeks. Analyses include internal consistency (Cronbach's alpha), test-retest reliability, and convergent/discriminant validity. Cronbach's alpha and test-retest reliability ≥0.7 were considered acceptable. Results: Mean age of the 311 men was 62±7. All domains of the RPQ demonstrated strong internal consistency (Cronbach's alpha=0.70-0.98) and test-retest reliability (ICC= 0.82-0.99). There was sound convergent validity for the RPQ EF domains with/without medication demonstrate by correlations with the IIEF Erectile Function Domain (EFD) (r=0.31 to 0.70, p<.05). Discriminate validity was demonstrated for RPQ EF domains with/without medication with moderate correlations with the SEAR and PROMIS scales (r=0.23 to r=0.59, p<.01). There was also sound convergent validity for RPQ SD, O, and SS domains with strong correlations with the PROMIS desire, orgasm, and satisfaction scales (r=0.66 to r=0.77, p<.01), with discriminant validity demonstrating moderate correlations with SEAR Self-Esteem (r=0.38 to r=0.46, p<.01) and Sexual Bother (r=-0.43 to 0.66, p<.01). The RPQ PM domain demonstrated convergent validity with moderate correlations with the IIEF EFD and Orgasm domain (r=-0.20; r=0.33, p<.01, respectively) and discriminant validity with low, non-significant correlation with EPIC Urinary function. Conclusion: Initial validation of the RPQ supports the reliability and validity of the scale. Disclosure: Work supported by industry: no.